Social Justice and Right of Access to Justice for Persons with Intellectual Disabilities - Boyuklieva, Iliana (Yearbook of the Law Department, 2022)
The present study focusses on Martha Nussbaum’s theory of social justice and the capabilities approach, their relevance to the legal protection of people with disabilities, and especially to their access to justice. I argue that this theory and approach present a new theoretical paradigm in which we can conceptualize and implement human rights of persons with intellectual disabilities. I pay attention to the right of access to justice, since it is the precondition and the guarantee for the protection of all other rights of people with disabilities in the rule of law.